Origins and History of Laboratory Insect Stocks in a Multispecies Insect Production Facility, With the Proposal of Standardized Nomenclature and Designation of Formal Standard Names. Issue 2 (1st May 2018) - Roe, Amanda D; Demidovich, Misha; Dedes, John
Abstract: Laboratory insect colonies are an essential part of experimental insect science. Formalized naming of laboratory stocks is standard practice in model organisms such as mice and fruit flies, but crucial details such as colony origin and standard names are often lacking in nonmodel systems. For institutions involved in rearing multiple nonmodel species, effective monitoring requires standardized naming and nomenclature, from establishment to production, distribution, and publication. Insect rearing has been the cornerstone of the Insect Production and Quarantine Laboratories (IPQL) at the Great Lakes Forestry Centre for over 70 yr, but the histories of the insect colonies in this facility have not been adequately documented and formal, standardized names do not exist. We propose a standardized naming framework that we applied to the eight species reared at the IPQL to rectify these deficiencies. We also present the origin and history of each colony, essential information that is challenging to obtain post hoc. We suggest that other research institutions consider developing similar standards, so they can accurately document, communicate, and track laboratory insect their within the facilities and through the scientific literature.